Aplikasi Edukasi Gizi Remaja (Ezima) Efektif Meningkatkan Pengetahuan dan Sikap Mengonsumsi Sugar Sweetened Beverages Pada Remaja - Kadewi, Ami; Fauziah, Munaya; Sutini, Titin; P, Nyimas Heny; Purnawati, Tri (Universitas Malahayati, 2025)
ABSTRACT Sugar sweetened beverages (SSB) are packaged drinks that add sweeteners, as one of the ingredients in drinks with little nutritional content. Teenagers have a habit of consuming SSB. If it is not immediately anticipated, it can cause nutritional disorders and can cause health problems. Educational media is very important to increase knowledge and attitudes of teenagers consuming SSB. The aim of the research is to determine the difference in the influence of adolescent nutrition education using the EZIMA application and booklets on knowledge and attitudes towards consuming sugar sweetened beverages (SSB) in adolescents. This research design uses quasi experimental with two group pre and post test. The sample in this study was 100 respondents obtained from g-power calculations by entering an effect size of 0.8, α err prob 0.05, power 0.80, divided into two groups, namely education based on the EZIMA application and booklets with 50 respondents each. The instrument used in this research was a questionnaire for knowledge and attitudes. The paired t-test showed that there was a difference in respondents' knowledge before and after being given education on the EZIMA application with a p-value of 0.021 and the booklet group had a p-value of 0.012. There is a difference in respondents' attitudes before and after with a p-value of 0.038 for the EZIMA application and a p-value of 0.016 for the booklet. The results of the independent t-test in the educational intervention group based on the EZIMA application were with a p-value of 0.002, in the intervention group using booklets with a p-value of 0.001. There is a difference in knowledge and attitudes towards consuming SSB among adolescents in educational interventions based on the EZIMA application and booklet. The results of this research can be used in education based on the EZIMA application for nursing services as educational material in increasing knowledge and attitudes towards consuming SSB in adolescents. Keywords: Sugar-Sweetened Beverages, Knowledge, Attitude, EZIMA Application, Booklet. ABSTRAK Sugar sweetened beverages (SSB) adalah minuman dalam kemasan yang ditambahkan pemanis, sebagai salah satu bahan dalam minuman dengan sedikit kandungan nutrisi. Remaja mempunyai kebiasaan mengonsumsi SSB bila tidak segera diantisipasi maka dapat menyebabkan gangguan gizi dan dapat menyebabkan gangguan kesehatan. Media edukasi sangat penting untuk meningkatkan pengetahuan dan sikap remaja mengonsumsi SSB. Tujuan dari penelitian mengetahui perbedaan pengaruh edukasi gizi remaja menggunakan aplikasi EZIMA dan booklet terhadap pengetahuan dan sikap mengonsumsi Sugar sweetened beverages (SSB) pada remaja. Desain penelitian ini menggunakan quasi experimental dengan two group pre and post test. Sampel pada penelitian ini sejumlah 100 responden yang didapat dari perhitungan g-power dengan memasukkan effect size 0.8, α err prob 0.05, power 0.80 dibagi menjadi dua kelompok yaitu edukasi berbasis aplikasi EZIMA dan booklet masing-masing 50 responden. Instrumen yang digunakan dalam penelitian ini adalah kuesioner untuk pengetahuan dan sikap. Uji uji paired t- test didapatkan ada perbedaan pengetahuan responden sebelum dan sesudah diberikan edukasi aplikasi EZIMA dengan p-value 0,021 dan kelompok booklet p value 0,012. Terdapat perbedaan sikap responden sebelum dan sesudah dengan p-value 0,038 aplikasi EZIMA dan p-value 0,016 booklet. Hasil uji independent t-test pada kelompok intervensi edukasi berbasis aplikasi EZIMA dengan p-value 0,002, pada kelompok intervensi menggunakan booklet dengan p-value 0,001. Terdapat pengaruh perbedaan pengetahuan dan sikap mengonsumsi SSB pada remaja pada intervensi edukasi berbasis aplikasi EZIMA dan booklet. Hasil penelitian ini dapat digunakan edukasi berbasis aplikasi EZIMA untuk layanan keperawatan sebagai bahan edukasi dalam meningkatkan pengetahuan dan sikap mengonsumsi SSB pada remaja. Kata Kunci: Sugar-Sweetened Beverages, Pengetahuan, Sikap, Aplikasi EZIMA, Booklet.